Digitization and sustainability: Practical convergences of two leading discussions in business law - Anne-Christin Mittwoch (Martin-Luther-Universität Halle-Wittenberg, Institut für Wirtschaftsrecht, Forschungsstelle für Transnationales Wirtschaftsrecht, 2024)
Until now, digitization and sustainability have stood side by side in the discussion of business law. As leading discourses of the present-day business scene, both topics are leading to profound change in companies and are influencing each other in the process - a circumstance that can no longer be ignored by corporate management. The article shows the guiding ideas behind both discussions, as well as their convergences and interactions, and asks about the effects they have on management's duty to act. – – Bislang stehen Digitalisierung und Nachhaltigkeit in der wirtschaftsrechtlichen Diskussion allzu oft nebeneinander. Als Leitdiskurse der Gegenwart führen beide Themen jedoch zu tiefgreifenden Veränderungen in Unternehmen und beeinflussen sich dabei gegenseitig - ein Umstand, den Unternehmensführungen nicht länger ignorieren können. Der Beitrag zeigt die Leitideen der beiden Diskurse, ihre Konvergenzen und Wechselwirkungen auf und fragt nach den Auswirkungen auf die Handlungspflichten des Managements.
Keywords: 340; Sustainability; Digitization; Corporate Sustainability; Corporate Digital Responsibility; Directors' Duties